2015
DOI: 10.1002/jts.22040
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Israeli Children Exposed to Rocket Attacks: Assessment, Risk, and Resilience

Abstract: Preschool children are among the most vulnerable populations to adversity. This study described the effects of 4 weeks of daily exposure to rocket attacks on children living on Israel's southern border. Participants enrolled in this study were 122 preschool children (50% boys) between the ages 3 and 6 years from 10 kindergartens. We assessed mothers' report of children's symptoms according to the DSM-IV and alternative criteria resembling the DSM-5 criteria for posttraumatic stress disorder (PTSD), general ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The characteristics of the included studies are shown in Table 2 . 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Participants ranged in age from 0 to 16 years. Three studies included children more than 6 years of age, but had a total mean age of less than 6.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the included studies are shown in Table 2 . 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 Participants ranged in age from 0 to 16 years. Three studies included children more than 6 years of age, but had a total mean age of less than 6.5 years.…”
Section: Resultsmentioning
confidence: 99%
“… 47 2012 Medical illness Single Non-interpers Ind– 3-16 y (6.5 y, 2.8) Wh (92), Bl (<1), As (2), Mx/Oth (5) 245 42 >36 DAWBA DSM-IV Med (8) Wolmer et al. 48 2015 War Repeat Interpers Grp– 3-6 (64.12 mo, 8.48) DNR 122 50 >3 PTSDSSI PTSD-AA High (4) Note: Af Am = African American; As = Asian; Bl = Black; CPTSD-RI = Childhood PTSD Reaction Index; DAWBA = Development and Well-Being Assessment; DICA-P = Diagnostic Interview for Children and Adolescents; DIPA = Diagnostic Infant and Preschool Assessment; DNR = did not report; Eu Am = European American; Hi = Hispanic; IPV = interpersonal violence; Isr = Israeli; Jap = Japanese; Lat = Latino/a; Mx = mixed; Oth = other; PAPA = Preschool Age Psychiatric Assessment; PTSD-AA = PTSD Alternative Algorithm; PTSDSSI = PTSD Semi-Structured Interview; SSIORIYC = Semi-Structured Interview and Observational Record for Infants and Young Children; Unk = unknown; Wh = White. a Average time since trauma.…”
Section: Resultsmentioning
confidence: 99%
“…This gloomy proposition is reinforced by the enlightening study by Feldman and Vengrober (2011) who investigated 232 infants and young children aged 1.5–5, 148 of whom were from the war zone of Sderot in Israel (located 10 km from the Gaza border and has been exposed repeatedly to heavy Hamas rocket attacks over a period of several years), whereas the rest of the participants were from non‐war zone areas in Israel. They found that a large proportion of young children (about 40%) of those who were raised in a war zone and exposed to daily shooting, rockets, or missile attacks, were likely to develop Post‐Traumatic Stress Disorder (PTSD), with frequent symptoms of inconsolability and agitation, repeated expressions of trauma in daily life, and substantial developmental regression (see also Wolmer et al., 2015).…”
Section: The Context Of Intractable Conflictmentioning
confidence: 99%
“…Displacement as a result of political conflicts or natural disasters creates significant amounts of stress on the young child as well as on the entire family system, due to the loss of the usual routines, schools, health care and economic instability. The vulnerability of a preschool child to the experience of a significant traumatic event is also determined by the accumulation of stressful life events such as migration, the birth of a sibling, the death of family members, parental divorce, or violence in the home 11 .…”
Section: Outcome and Moderating Factorsmentioning
confidence: 99%
“…Assessment of preschool children ought to consider their limited verbal abilities and the fact that parents are more likely to notice their symptoms (e.g., sleep disturbance, separation difficulties) 11,19,20 . Screening tools 25 are critical to identifying the specific criteria of preschoolers' posttraumatic stress that have been recently adapted 26 .…”
Section: Assessmentmentioning
confidence: 99%